Influence of Arctic Sea Ice Loss in Autumn Compared to That in Winter on the Atmospheric Circulation - Russell Blackport; James A. Screen (Geophysical Research Letters, 2019)
Abstract There is growing evidence that Arctic sea ice loss affects the large‐scale atmospheric circulation. Some studies suggest that reduced autumn sea ice may be a precursor to severe midlatitude winters. Here we use coupled ocean–atmosphere model experiments to investigate the extent to which the winter atmospheric circulation response to Arctic sea ice loss is driven by sea ice loss in preceding months. We impose different seasonal cycles of sea ice by using various combinations of sea ice albedo parameters. Year‐round sea ice loss causes an equatorward migration of the eddy‐driven jet and a shift toward the negative phase of the North Atlantic Oscillation in winter. However, these circulation changes are not found when sea ice is reduced only in late summer and autumn, despite high‐latitude warming persisting into the winter. Our results imply that the winter atmospheric circulation response to sea ice loss is primarily driven by sea ice loss in winter rather than in autumn.